Corporate Governance 2010
DOI: 10.1002/9781118258439.ch19
|View full text |Cite
|
Sign up to set email alerts
|

The Governance of Family Firms

Abstract: In the last decade, corporate governance research has documented that families control most publicly-traded firms around the world. This finding has triggered a considerable body of research that seeks to understand the governance of family firms and their impact on firm performance. This chapter critically examines this literature. The chapter highlights that the main governance issue facing family firms is balancing the benefits associated to having a controlling family with the challenges this structure imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 76 publications
2
56
0
Order By: Relevance
“…These studies show that family firms are relatively less frequent in sectors with high capital intensity and scale (Bennedsen et al, 2010), as well as in those sectors where family firm-specific investments are not crucial, as in rapidly evolving industries or in R&D-intensive industries (Pérez-González, 2006), or in markets that are larger in size (Demsetz and Lehn, 1985;Villalonga and Amit, 2010). In almost all these papers, the absence of a direct measure of individual risk preferences makes capital intensity a proxy for individual risk attitude at the organizational level.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 2 more Smart Citations
“…These studies show that family firms are relatively less frequent in sectors with high capital intensity and scale (Bennedsen et al, 2010), as well as in those sectors where family firm-specific investments are not crucial, as in rapidly evolving industries or in R&D-intensive industries (Pérez-González, 2006), or in markets that are larger in size (Demsetz and Lehn, 1985;Villalonga and Amit, 2010). In almost all these papers, the absence of a direct measure of individual risk preferences makes capital intensity a proxy for individual risk attitude at the organizational level.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…As families make decisions that maximize the welfare of the family, the joint maximization of family and business objectives often entail gains in one sphere at the expense of the other one (Bennedsen et al, 2010). Empirical literature has shown that family ownership has important implications for corporate management and performance (Shleifer and Vishny, 1997).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies that have addressed these factors have only studied family firms, and usually study the effect these factors can have on incentives to mitigate agency problems. For example, authors have shown variations in that relationship when introducing mediating variables, as is the case when considering the generation in control [30,42,43], family management involvement [37,44,45], provision of incentives [46], and when distinguishing between lone-founder and family firms [43,47]. Thus, it is increasingly important to study the way in which these factors function in order to discover the nuances that make them successful for family firms and unsuccessful for non-family firms, and vice versa.…”
Section: Effect Of Other Factors On Performancementioning
confidence: 99%
“…Previous literature clearly emphasizes the importance of studying heterogeneity among family firms by pointing out that the variance in family firm behaviors is greater than the variance in behaviors between family firms and their non-family counterparts (e.g., Bennedsen, Perez-Gonzalez & Wolfenzon, 2010). It has been observed that the key governance conditions, namely, the characteristics of family ownership and control, the involvement of family members in the top management team (TMT) and the participation of later generations (Miller & Le Breton-Miller, 2006), are major sources of family firm's heterogeneity (Chua, Chrisman, Steier, & Rau, 2012;Li & Daspit, 2016), because they are associated with different organizational goals, processes and routines (e.g., Carney, 2005;Le Breton-Miller & Miller, 2006;Li & Daspit, 2016).…”
Section: Introductionmentioning
confidence: 99%